The Contribution of Artificial Intelligence to Addressing the Global Goals for Sustainable Development - Hany Fathy Abdel-Elaah; Amira Hassan Abed (PT. Delitekno Media Madiri, 2025)
The increasing prevalence of Artificial Intelligence (AI) across various industries necessitates an assessment of its impact on achieving the Sustainable Development Goals (SDGs). Studies indicate that AI has the potential to support 134 targets across all goals through professional, consensus-based data collection strategies. However, it may also hinder progress toward 59 targets, presenting a complex interplay between benefits and challenges. Key concerns include gaps in safety, transparency, and ethical standards, which arise when regulatory frameworks fail to keep pace with the rapid advancement of AI technologies. These issues highlight the need for robust governance and oversight mechanisms to address potential risks. Additionally, overlooked components in the study, such as social equity, environmental justice, and accessibility, are critical for ensuring AI-based solutions contribute effectively to sustainable growth. This research emphasizes the importance of aligning AI applications with global regulatory and ethical standards to maximize positive outcomes while mitigating adverse effects. By fostering collaboration among policymakers, industry leaders, and researchers, AI can become a transformative tool for achieving SDGs. Future efforts should prioritize addressing regulatory gaps and ensuring that AI-driven innovation remains inclusive, transparent, and aligned with the core principles of sustainability.